Bone Tumor Suppression in Rabbits by Hyperthermia below the Clinical Safety Limit Using Aligned Magnetic Bone Cement. Issue 3 (4th December 2021) - Yu, Xiang; Gao, Shan; Wu, Di'an; Li, Zhengrui; Mi, Yan; Yang, Tianyu; Sun, Fan; Wang, Lichen; Liu, Ruoshui; He, Shuli; Ge, Qinggang; Lv, Yang; et al.
Abstract: Demonstrating highly efficient alternating current (AC) magnetic field heating of nanoparticles in physiological environments under clinically safe field parameters has remained a great challenge, hindering clinical applications of magnetic hyperthermia. In this work, exceptionally high loss power of magnetic bone cement under the clinical safety limit of AC field parameters, incorporating direct current field‐aligned soft magnetic Zn0.3 Fe2.7 O4 nanoparticles with low concentration, is reported. Under an AC field of 4 kA m −1 at 430 kHz, the aligned bone cement with 0.2 wt% nanoparticles achieves a temperature increase of 30 °C in 180 s. This amounts to a specific loss power value of 327 W g m e t a l − 1 and an intrinsic loss power of 47 nHm 2 kg −1, which is enhanced by 50‐fold compared to randomly oriented samples. The high‐performance magnetic bone cement allows for the demonstration of effective hyperthermia suppression of tumor growth in the bone marrow cavity of New Zealand White Rabbits subjected to rapid cooling due to blood circulation, and significant enhancement of survival rate. Abstract : A record high specific loss power of 327 W g ‐1 metal and intrinsic loss power of 47 nHm 2 kg ‐1 are achieved under an alternating current field of 4 kA m ‐1 and 430 kHz, under the clinical safety limit, in magnetic bone cement incorporating a low concentration of field‐aligned Zn0.3 Fe2.7 O4 nanoparticles. Hyperthermia suppression of osteosarcoma and significant enhancement of survival rate in rabbits are demonstrated.